2019
DOI: 10.1093/molehr/gaz026
|View full text |Cite
|
Sign up to set email alerts
|

Reduced inflammatory state promotes reinnervation of endometriotic-like lesions in TNFRp55 deficient mice

Abstract: Endometriosis is a chronic gynecological disease, characterized by growth of endometrial tissue in ectopic sites due to alteration of peritoneal homeostasis and deregulation of apoptosis. Here we have examined whether TNFRp55 deficiency modulates the pro-inflammatory state and the reinnervation of endometriotic-like lesions in mice. Two-month-old female C57BL/6 mice, eight wild type (WT) and eight TNFRp55−/− (KO) were used in the study. Endometriotic-like lesions were induced experimentally. The right uterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…We found that the surgical establishment of EDT in mice increased the concentrations of Cu and estradiol, and the administration of a Cu chelating drug decreased both concentrations to values similar to the group with placebo surgery [208]. We also found similar results in another study [209], in which elevated Cu and estradiol levels were efficiently reduced by a Cu chelator in a murine model deficient in tumor necrosis factor (TNF-α) receptor 1 (TNFR1), which presents an aggravated state of EDT [202,210,211].…”
Section: 'Benign' Diseasessupporting
confidence: 77%
“…We found that the surgical establishment of EDT in mice increased the concentrations of Cu and estradiol, and the administration of a Cu chelating drug decreased both concentrations to values similar to the group with placebo surgery [208]. We also found similar results in another study [209], in which elevated Cu and estradiol levels were efficiently reduced by a Cu chelator in a murine model deficient in tumor necrosis factor (TNF-α) receptor 1 (TNFR1), which presents an aggravated state of EDT [202,210,211].…”
Section: 'Benign' Diseasessupporting
confidence: 77%
“…It is important to mention that, in the absence of TNFR1, all TNFR2-dependent pathways become relevant, particularly those related to cell proliferation, survival, and angiogenesis 8 . In fact, in a previous study carried out in TNFR1 −/− animals, it was found that there was greater activation of NF-κB than in wild-type animals 14 . Therefore, we postulate that, in the absence of TNFR1, there is not only an interruption of the recognized crosstalk between both TNFRs 10 but also an alteration of TNFR2 signaling by TM.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the TNFR2 levels and TNF-α increased as EDT worsened 13 . We previously showed that, in TNFR1-deficient mice, a worsening of pathology is observed compared to the EDT progression in wild-type mice 5 , 6 , 14 .…”
Section: Introductionmentioning
confidence: 98%
“…The increase in neurotrophic factors may be responsible for stimulating nerve development and boosting the growth of sensory nerves (Ref. 29). Further research into the specific mechanisms, NGFs in rats' ovaries were found to affect the expression of neurotransmitter-related enzymes in noradrenergic and cholinergic systems, causing the corresponding neurotransmitter content to change and subsequent cascade response (Ref.…”
Section: Neurogenesis and Endometriosismentioning
confidence: 99%